A Role for Yeast/Pseudohyphal Cells of Candida albicans in the Correlated Expression of NLRP3 Inflammasome Inducers in Women With Acute Vulvovaginal Candidiasis - Roselletti, Elena; Monari, Claudia; Sabbatini, Samuele; Perito, Stefano; Vecchiarelli, Anna; Sobel, Jack D.; Cassone, Antonio (Frontiers in Microbiology, 2019)
In acute vulvovaginal candidiasis (VVC), the fungus Candida albicans activates inflammasome receptors of vaginal epithelial cells through the production of virulence and immuno-inflammatory factors. Here we show thatin VVC patients, genes encoding some of the above factors (SAP2, SAP5, SAP6, ECE1 and HWP1) are expressedin a correlated fashion. Cytological observations pointed out that pseudo-hyphal filaments with yeast cells are dominantat the acidic vaginal pH, and this is coupled with co-expression, at roughly similar level, of SAP2, a typical yeast- and ECE1, a typical hyphae-associated genes. In contrast, vigorous hyphal growth dominated at the neutral vaginal pH of mice experimentally infected with C. albicans isolates from VVC subjects, and this is coupled with a high ratio of ECE1 to SAP2 expression. We suggest the pseudo-hyphal rather than true hyphal cells of C. albicans play a critical role in VVC, possibly through the activity of multiple inflammasome inducers.